Macroeconomic and Sectoral Effects of the EAC Regional Integration on Uganda: A Recursive Computable General Equilibrium Analysis - Shinyekwa, Isaac; Mawejje, Joseph (Economic Policy Research Centre (EPRC), 2013)
The paper empirically examines the implications of the implementation of the EAC regional integration on the Ugandan economy. Specifically, it analyses the likely effects of the asymmetric tariff reduction on the macro variables and quantifies the sectoral growth effects on the industrial, agricultural and services sectors. It adopts the General Equilibrium Model (CGE) for the analysis based on the Uganda 2007 Social Accounting Matrix. The primary policy simulation is the asymmetric reduction of internal tariffs across East African countries under assumptions of unemployment and free movement of factors of production. Other policy simulations that change these assumptions are analysed. Results indicate that the aggregate impact of internal tariff reduction under conditions of unemployment and free movement of factors of production is positive with average GDP growth improving by up to 0.3 percentage points over the period 2008 – 2021. However, the reduction in tariffs has negative implications for tax collections with import duties contracting by 0.3 percentage points, with no significant gains in direct taxes revenues. The rise in exports to the EAC region leads to a decline in the trade deficit by 0.8 percent during the simulation period. There are also significant growth gains for agriculture, industry and services sectors with the former registering growth improvements of 1.2 percentage points and the other two 0.7 percentage points. Therefore, Uganda should optimise gains within the EAC regional integration framework through tariff reduction and free movement of factors of production. Finally, the government should address infrastructural constraints (energy and transport) to foster growth in the manufacturing sector within the EAC region.